The Effect of Changes in Work Patterns and Sleep Quality on Regular Workers of Pertamina Up Stream Energy West Madura Offshore (PHE 5 WMO) on Complaints of Physical and Mental Work Examination - Van Satrio Wibowo; Indriati Paskarini (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
8 out of 10 employees of Pertamina Hulu Energi 5 West Madura Offshore (PHE 5 WMO) have complaints of difficulty in concentration. These complaints were felt by the workers since there was a change in work patterns from 2 weeks of work and 2 weeks off to 4 working weeks and 4 weeks off. The purpose of this study was to analyze the factors that influence complaints of physical and mental work fatigue due to changes in work patterns in regular PHE 5 WMO workers. This study is a sectional technique of Stratified Random Sampling sampling 67 workers. The variables in this study were age, sleep quality, and complaints of physical and mental work fatigue. Individual characteristic data was obtained using a questionnaire. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Complaints of physical and mental work fatigue were measured using the Industrial Fatigue Research Committee of the Japanese Association of Industrial Health (IFRC Japan) questionnaire. Data were analyzed by a logistic regression test. obtained a regression coefficient of 1.896 with a Wald value of 7.278 and a significance value of 0.007. These results show a significance value of less than 0.05 (sig < 0.05) so that it is stated that there is a significant influence between sleep quality on complaints of physical and mental fatigue, meaning that the worse sleep quality will have a significant effect on the higher complaints of physical and mental fatigue.